EGFR mutation detection in NSCLC-assessment of diagnostic application and recommendations of the German Panel for Mutation Testing in NSCLC - Penzel, Roland; Sers, Christine; Chen, Yuan; Lehmann-Mühlenhoff, Ulrich; Merkelbach-Bruse, Sabine; Jung, Andreas; Kirchner, Thomas; Büttner, Reinhard; Kreipe, Hans H.; Petersen, Iver; Dietel, Manfred; Schirmacher, Peter (Virchows Archiv, 2011)
EGFR mutation testing in non-small cell lung cancer (NSCLC) is a novel and important molecular pathological diagnostic assay that is predictive of response to anti-epidermal growth factor receptor (EGFR) therapy. A comprehensive compilation of a large number of EGFR mutation analyses of the German Panel for Mutation Analyses in NSCLC demonstrates (a) a higher than previously reported mutation frequency outside the conventionally tested exons 19 and 21 and (b) an overall superiority of sequencing based assays over mutation-specific PCR. The implications for future diagnostic EGFR mutation testing are discussed.